Enriched environment ameliorates adult hippocampal neurogenesis deficits in Tcf4 haploinsufficient mice - Braun, Kristina; Häberle, Benjamin; Wittmann, Marie-Theres; Lie, Dieter Chichung (BMC Neuroscience, 2020)
Background: Transcription factor 4 (TCF4) has been linked to human neurodevelopmental disorders such as intellectual disability, Pitt-Hopkins Syndrome (PTHS), autism, and schizophrenia. Recent work demonstrated that TCF4 participates in the control of a wide range of neurodevelopmental processes in mammalian nervous system development including neural precursor proliferation, timing of differentiation, migration, dendritogenesis and synapse formation. TCF4 is highly expressed in the adult hippocampal dentate gyrus – one of the few brain regions where neural stem / progenitor cells generate new functional neurons throughout life. Results: We here investigated whether TCF4 haploinsufficiency, which in humans causes non-syndromic forms of intellectual disability and PTHS, affects adult hippocampal neurogenesis, a process that is essential for hippocampal plasticity in rodents and potentially in humans. Young adult Tcf4 heterozygote knockout mice showed a major reduction in the level of adult hippocampal neurogenesis, which was at least in part caused by lower stem/progenitor cell numbers and impaired maturation and survival of adult-generated neurons. Interestingly, housing in an enriched environment was sufficient to enhance maturation and survival of new neurons and to substantially augment neurogenesis levels in Tcf4 heterozygote knockout mice. Conclusion: The present findings indicate that haploinsufficiency for the intellectual disability- and PTHS-linked transcription factor TCF4 not only affects embryonic neurodevelopment but impedes neurogenesis in the hippocampus of adult mice. These findings suggest that TCF4 haploinsufficiency may have a negative impact on hippocampal function throughout adulthood by impeding hippocampal neurogenesis.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Adult neurogenesis; Enriched environment; Hippocampus; Intellectual disability; PTHS; Tcf4

Neoadjuvant Radiochemotherapy Alters the Immune and Metabolic Microenvironment in Oral Cancer—Analyses of CD68, CD163, TGF-β1, GLUT-1 and HIF-1α Expressions - Weber, Manuel; Ries, Jutta; Braun, Kristina; Wehrhan, Falk; Distel, Luitpold; Geppert, Carol-Immanuel; Lutz, Rainer; Kesting, Marco Rainer; Trumet, Leah (Cells, 2024)
Background: The first-line treatment of oral squamous cell carcinoma (OSCC) involves surgical tumor resection, followed by adjuvant radio(chemo)therapy (R(C)T) in advanced cases. Neoadjuvant radio- and/or chemotherapy has failed to show improved survival in OSCC. Recently, neoadjuvant immunotherapy has shown promising therapeutic efficacy in phase 2 trials. In this context, the addition of radio- and chemotherapy is being reconsidered. Therefore, a better understanding of the tumor-biologic effects of neoadjuvant RCT would be beneficial. The current study was conducted on a retrospective cohort of patients who received neoadjuvant RCT for the treatment of oral cancer. The aim of the study was to evaluate the influence of neoadjuvant RCT on the immunological tumor microenvironment (TME) and hypoxic and glucose metabolisms. Methods: A cohort of 45 OSSC tissue samples from patients were analyzed before and after RCT (total 50.4 Gy; 1.8 Gy 5× weekly; Cisplatin + 5-Fluorouracil). Immunohistochemistry for CD68, CD163, TGF-β, GLUT-1 and HIF-1α was performed using tissue microarrays and automated cell counting. Differences in expression before and after RCT and associations with histomorphological parameters (T-status, N-status) were assessed using the Mann–Whitney U test. Results: Tumor resection specimens after neoadjuvant RCT showed a significant decrease in CD68 infiltration and a significant increase in CD163 cell density. The CD68/CD163 ratio was significantly lower after RCT, indicating a shift toward M2 polarization. The GLUT-1 and HIF-1α expressions were significantly lower after RCT. Larger tumors (T3/T4) showed a lower GLUT-1 expression. Other biomarkers were not associated with the T- and N-status. Conclusions: Neoadjuvant RCT with 50.4 Gy induced a shift toward the M2 polarization of macrophages in the TME. This change in immune composition is not favorable and may be prognostically negative and counteract immunotherapeutic approaches. In addition, the decreased expressions in GLUT-1 and HIF-1α indicate reductions in the glucose metabolism and hypoxic energy metabolism in response to “high dose” neoadjuvant RCT, which may be therapeutically desirable.
CRIS-Team Scopus Importer:2024-03-22
Keywords: head and neck squamous cell carcinoma; HNSCC; hypoxia; immune tolerance; induction therapy; macrophage polarization; metabolism; oral squamous cell carcinoma; OSCC; RCT